Bibliometric Trends of Science, Technology, Engineering, Mathematic Integration and Science Process Skills Development through Sustainable Seed Paper for SDGs - Nensy Eka Selviana; Endang Susantini; Lidya Vriska Fatimah Azzahra; Muhammad Zahrudin Afnan; Rinaldiyanti Rukmana; Erti Hamimi (Jurnal Pendidikan Sains Indonesia, 2026)
This research examines the incorporation of scientific process skills within science, technology, engineering, and mathematic (STEM) education, focusing particularly on sustainability and the insufficient alignment among teaching methodologies, skill enhancement, and eco-friendly educational resources. A mixed-methods approach was utilized, integrating bibliometric analysis with a systematic literature review to uncover publication trends, key themes, and research deficiencies in STEM education, scientific process skills, and sustainability. Data were collected from the Scopus database using the search terms "science process skills" and "STEM" for publications spanning from 2005 to 2025. Out of an initial pool of 1.250 documents, 101 articles fulfilled the inclusion criteria, with 13 highly pertinent studies analyzed in detail. The bibliometric results indicate that STEM research primarily focuses on instructional methods and pedagogical approaches, while relatively little emphasis is placed on the creation of practical, sustainability-focused educational media. Qualitative analysis further suggests that eco-friendly learning materials are still underused in STEM education, despite their capacity to improve project-based and authentic learning experiences. Consequently, this study advocates for the adoption of seed paper as a novel and sustainable teaching medium to enhance scientific process skills. The results underscore considerable prospects for promoting sustainable STEM education that aligns with 21st-century competencies and the fulfillment of SDG 4 and SDG 12